(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Diabetes is among the most common chronic illnesses worldwide, with escalating rates around the world. Four years after the launch of liraglutide (a human GLP-1 analogue for type 2 diabetes) we aimed to evaluate the impact of its use in terms of resources consumption and also in terms of some clinical outcomes. Methods A budget impact model (BIM) has been developed. The model was used to assess the financial impact for the Italian NHS caused by an increased use of liraglutide in patients with type 2 diabetes (T2DM). The analysis was conducted in a 3-year time horizon considering year 2013 as baseline. We used real data of market consumption, reflecting the budget holder’s perspective, and not just a hypothetical cohort of patients. Results Increasing the percentage of patients receiving liraglutide over the next 3 years, would lead to an increase of costs, ranging from €2.1 million in the first year to €6.7 million in the third year for a total of €13.7 million. However, for these additional costs, the Italian NHS would get more patients with glycaemic control. Conclusions This study has shown that an increase in the use of liraglutide would determine a relatively low extra cost per patient with T2DM in the Italian NHS. The results could be considered conservative since we did not include savings associated to a reduction of hypoglycaemic events. More comprehensive assessments, considering total costs of treatment and expected health benefits, can help decision-makers analyse whether higher acquisition costs may be offset by higher therapeutic results, leading to future projected savings for the healthcare system.